Remote Sensing Method for Extracting Topographic Information on Tidal Flats Using Spatial Distribution Features. Issue 5 (3rd September 2021) - Lijun, Yang; Yao, Xiao; Jie, Jiang; Yixiang, Chen; Yan, Gu; Sentong, Zhang
Abstract: A remote sensing method combining remote sensing and ground surveying is proposed to extract tidal flat topographic information via the spatial distribution characteristics of tidal flat surface features. Based on the eastern Chongming beach of the Yangtze Estuary and Landsat-5 satellite images, this study identifies the spatial distribution characteristics of tidal flat features using field-based RTK data and spectral data. The remote sensing method for extracting the geometric and physical characteristics of linear and surface geographical elements on tidal flats and the elevation assignment method are discussed. The effectiveness of this method is verified by the quality of the resultant tidal flat DEM. The results show that the use of spatial distribution features in remote sensing images can provide rich topographic information. The DEM results have an accuracy of 0.16 m, are in line with the basic topographic patterns of tidal flats, and can describe local microscale geomorphic features. This technique solves the problem of a single topographic information source in current remote sensing measurement methods and provides technical support for detecting dynamic changes in coastal zones by using remote sensing technology.